2004
DOI: 10.1093/brief-treatment/mhh027
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Trauma Therapist: A Qualitative Study of the Child Therapist's Perspectives and Experiences

Abstract: Although there is increasing literature on secondary traumatic stress, little is known about the therapist's perspective and experience in working with traumatized children. This qualitative study utilized an interpretivist paradigm to understand therapists' experiences in working with such children. Interviews suggest that therapists perceive common issues related to treatment, impact of the therapeutic work, and the importance of making personal meaning of their work. Most importantly, becoming a trauma spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Educating themselves about the field in general and, more specifically, about secondary traumatic stress, allows the mental health worker to understand that this is a common occurrence in the field, and reduces the stress of thinking they are not doing their job correctly if they are experiencing vicarious trauma (Lonergan et al, 2004).…”
Section: Personal Factors That Mitigate or Decrease Vicarious Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…Educating themselves about the field in general and, more specifically, about secondary traumatic stress, allows the mental health worker to understand that this is a common occurrence in the field, and reduces the stress of thinking they are not doing their job correctly if they are experiencing vicarious trauma (Lonergan et al, 2004).…”
Section: Personal Factors That Mitigate or Decrease Vicarious Traumamentioning
confidence: 99%
“…Therapists reported that having supervision and dedicated time to discuss their experiences assisted them (Lonergan et al, 2004;Pistorius, 2006;VanDeusen & Way, 2006).…”
Section: Organisational Factors That Mitigate or Decrease Vicarious Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Working with traumatised children may disrupt a psychotherapist's everyday life (Canfield, 2003) and includes frustration and difficulty in working with multiple, often fragmented systems in the child's life, for example, the challenges in working with legal, child protection, and foster care systems associated with sexually abused children (Pistorius, 2006) and/or specifically with children in the foster care system (Lonergan, O’Halloran, & Crane, 2004). The challenges for the psychotherapist and source of emotional difficulty include the family, dealing with systems in community health agencies (Edgeson, 2006), and being exposed to traumatic material.…”
mentioning
confidence: 99%
“…Although there is a growing body of research on retention, to date most research on the impacts of child protection work on staff have focused on conditions of adversity, been quantitative in nature, deficit-based, and developed from the perspective of psychopathology, (Adams, Boscarino, & Figley, 2006;Dunkley & Whelan, 2006;Linley & Joseph, 2005). Therefore an increased understanding of the experiences CPW not subject to symptoms of psychopathology and who remain committed to child protection work is warranted (Lonergan, O'Halloran, & Crane, 2004;Westbrook et al, 2006).…”
Section: Adversity Impacting Child Protection Workersmentioning
confidence: 99%